The role of serum monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) in cardiovascular disease risk - Kharazmi-Khorassani , Jasmin; Ghafarian Zirak , Roshanak; Ghazizadeh , Hamideh; Zare-Feyzabadi , Reza; Kharazmi-Khorassani , Sara; Naji-Reihani-Garmroudi, Sharzad; Kazemi , Elham; Esmaily , Habibollah; Javan-Doust, Ali; Banpour, Hamed; Mohammadi-Bajgiran, Maryam; Besharatlou, Mohhamad reza; et al. (Acta Biomedica Atenei Parmensis, 2021)
AbstractBackground:Fatty acids have been observed as independent risk factors of cardiovascular diseases (CVD). In this study we investigated FFA levels in patients with CVD, and, its risk factors.Material and Methods:In this case-control study, 346 unrelated Iranian patients who underwent coronary angiography were enrolled. Participants were categorized into two groups: who had >50% stenosis were assigned to the angiogram positive group (N=90) and those with